Adducin methylation and blood pressure in young adults ; less is more - Wan Omar, Wan Fatein Nabeila; A.Talib, Norlelawati; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; Abdullah, Aszrin (2020)
Background: Essential hypertension is a multifaceted disease implicating both genetic, environment and epigenetic modification. Whilst -Adducin (ADD1) polymorphism in essential hypertension has been previously described, modification in DNA methylation of ADD1 gene in hypertensive young adults is not known. Objective: To evaluate the association between ADD1 methylation and blood pressure in hypertensive young adults. Materials and methods: A cross-sectional study involving 80 normotension and 80 incident hypertension aged 18 to 45 years was conducted in Kuantan, Pahang. Subjects were recruited via purposive sampling according to blood pressure status. Anthropometric measurements and biochemical parameters (glycemic index, lipid profile, high- sensitivity C-reactive protein) were examined. ADD1 methylation in peripheral blood were assessed using MethyLight assay. Results: There were inverse correlation significant between ADD1 methylation and systolic blood pressure (p = 0.006, r = –0.240), diastolic blood pressure (p = 0.001, r= –0.281) and mean arterial pressures (p = 0.002, r = –0.270). Hypertensive young adults had significantly lower ADD1 methylation compared to normotensive controls (p = 0.005). After controlling for other baseline covariates, ADD1 methylation proved to be a significant predictor for hypertension in young adults (p = 0.020). Conclusion: In young adults, ADD1 methylation predicted hypertension. Thus, ADD1 methylation could serve as a future preventive and therapeutic target for hypertension, upkeeping the precision medicine notion.